Evaluation of herbicides action on plant bioindicators by genetic biomarkers: a review - de Souza, Cleiton Pereira [UNESP]; Guedes, Thays de Andrade [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Springer Nature, 2016)
The use of pesticides has increased worldwide, owing to the demand for products of good quality and to satisfy a growing population. Herbicides represent almost half of the total amount of pesticides used. Although important to the reduction of costs and an increase of productivity, their indiscriminate use, as well as that of the other pesticides, is a global environmental problem, since they affect the living organisms. To evaluate the damage caused by herbicides to the environment, different organisms have been used as bioindicators, especially higher plants, due to several advantages. This is a literature review on herbicidal actions in plant bioindicators, as assessed by genetic biomarkers. Also, the present manuscript aimed to characterize the main organisms (Allium cepa, Vicia faba and Tradescantia spp.) and the most used biomarkers (mitotic index, chromosome aberrations, micronuclei, sister chromatid exchange and mutations). We concluded that herbicides induce cytotoxicity and genotoxicity in the assessed bioindicators. The data corroborate the existing warnings of the risks that the indiscriminate and increasing use of pesticides poses to the environment and its biodiversity.
Keywords: Allium cepa; Genotoxicity; Tradescantia; Vicia faba